Multiple Intelligences in Classrooms: The Case of Okyeso Primary School in Cape Coast, Ghana (Journal of Education and Development, 2020)
The understanding of multiple intelligences in our schools is very paramount. Multiple intelligences unearth diverse inherent talents in children through interactions in the classrooms. The ability to tap these potentialities and capabilities facilitates their career paths and placements. Unfortunately the education system in Ghana precisely our pre- schools appear not to have adequately set up mechanisms to take advantage of multiple intelligences in children. There seems to be cognitively spread approach using one-sided performance appraisal to examine and assess children’s intellectual abilities. The paper therefore identifies multiple intelligences strategy as a missing link in classroom interactions. A careful look is to examine the potentialities in children by critical investigation whether there are diverse levels of abilities and processing skills to solve problems. The inquiry was a case study and a mixed method. Primary 3 class was used and sample selection of 20 children and 5 teachers was employed using the purposive technique. Observation and interview were the main instruments. Bar charts and percentage scores were analytical procedures for the quantitative data while the thematic approach was used as concurrent analytical tool for the qualitative data. Verification strategy was by triangulation. Results were so appealing that, both pupils and teachers were able to identify some areas of multiple intelligences in the classrooms. However, these traits and characteristics were exhibited unknowingly. It is recommended that talents in the classrooms should be tapped using holistic approach to assess children’s abilities.